(untitled) (Archives of Clinical Psychiatry, 2005)
There are descriptions of skin reactions secondary to antipsychotic use. We reported a case of erythema multiform associated with ziprasidone use in a 47-year-old female patient diagnosed with schizophrenia. The patient was receiving the medication (80 mg/day) for seven weeks, and the dose was increased to 120 mg/day. Seven days after the dose change, the patient presented pruritus and erythematosus lesions in trunk, upper and lower members. The medication was discontinued and there was a complete improvement of the lesions. We were unable to find previous reports of association between erythema multiform and ziprasidone.